1982
DOI: 10.1177/096032718200100310
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Solvent Abuse in Cases Referred to the Poisons Unit, Guy's Hospital, July 1980-June 1981

Abstract: 1 From July 1980 to June 1981, requests for information as to management or prognosis were received concerning 324 patients (219 male, 91 female) aged 3-31 y (median 15 y) in whom 'solvent abuse' was suspected. 2 The principal symptoms reported were unconsciousness (37), drowsiness (62), 'collapse' (7), convulsions (6), ataxia (35), chest pain (9), nausea/vomiting (20), renal impairment (3) and behavioural disturbances (84). At least 105 patients were admitted to hospital, and 1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Thus, in a group of 20 consecutive admissions reported by King (1982), coma was the presenting feature in five of them, epileptic con vulsions in three, dysarthria in five, and ataxia in the rest. These findings are in agreement with those of Francis et a! (1982) from the National Poisons Information Service, who received requests for information on 105 patients admitted to different hospitals in the UK.…”
Section: Acute Effectssupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, in a group of 20 consecutive admissions reported by King (1982), coma was the presenting feature in five of them, epileptic con vulsions in three, dysarthria in five, and ataxia in the rest. These findings are in agreement with those of Francis et a! (1982) from the National Poisons Information Service, who received requests for information on 105 patients admitted to different hospitals in the UK.…”
Section: Acute Effectssupporting
confidence: 94%
“…(1982) from the National Poisons Information Service, who received requests for information on 105 patients admitted to different hospitals in the UK. Impairment of consciousness appears to be quickly reversible in most cases (Streicher et a!, 1981;King, 1982), and only 19% of the 105 admissions reported by Francis et a! (1982) remained in hospital for more than 24 hours.…”
Section: Acute Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…Anecdotal evidence, incident reporting, and referrals to the Guy's Poisons Unit (Francis et al, 1982) all indicate that solvents in adhesives are the most widely used, and yet these account for only a small proportion of deaths, especially when death not directly due to the solvent are excluded. Our evidence therefore lends support to assertions (Release, 1981) that toluene inhalation carries less risk of sudden death; nevertheless it is clear that sudden death does occur as a result of toluene inhalation and that this practice is potentially dangerous.…”
Section: Discussionmentioning
confidence: 97%
“…Against this level of extent of solvent abuse the number of cases admitted to hospital is relatively few. In one year the Guy's Hospital Poisons Unit received 324 enquiries concerning patients in whom solvent abuse was suspected (Frances et al, 1982) and the Grampion data revealed only 21 cases in 1981 and 6 cases in 1982 reported by Accident & Emergency departments. Solvent abuse does not, therefore, generate a numerically large problem of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%